Pengembangan Modul Enviropreneur Sampah Berbasis Problem-Based Learning - Putri, Dini Resita; Sueb, Sueb; Saptasari, Murni (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: The development aims to produce a valid and practical module about Enviropreneur Sampah based on problem-based learning. The development uses the ADDIE model which has five steps, there are analysis, design, development, implementation, and evaluation. The validity of the modules is assessed by validators of teaching material experts, material experts, and field practitioners (teacher). The practicality of the module is assessed by the module user (student). The results of the analysis showed that the validity of the materials (content) was 100%, the validity of the teaching materials was 100%. The validity in the field practitioners (teacher) was 87.6%, and the practicality module was 81.54%. Based on the analysis results show that the developed module is valid and practical. The analysis shows that the module developed is valid and practical.Abstrak: Pengembangan bertujuan untuk menghasilkan modul enviropreneur sampah berbasis problem-based learning yang valid dan praktis. Penggembangan menggunakan model ADDIE yang mempunnyai lima tahap, yaitu analysis, design, development, implementation, dan evaluation. Kevalidan modul dinilai oleh validator ahli bahan ajar, ahli materi, dan praktisi lapangan (guru). Kepraktisan modul dinilai oleh penguna modul (siswa). Hasil analisis menunjukkan validitas materi 100%, validitas bahan ajar 100% dan validitas praktisi lapangan 87,6%, serta kepraktisan modul sebesar 81,54%. Berdasarkan hasil analisis menunjukkan bahwa modul yang dikembangkan valid dan praktis.